1968
DOI: 10.1037/h0025736
|View full text |Cite
|
Sign up to set email alerts
|

Short-form tests: A methodological review.

Abstract: Studies are reviewed in which some well-known clinical tests of intelligence are abbreviated to save testing time. Serious methodological problems are evident in most of these studies: samples are often small, unrepresentative, and heterogeneous in composition; and short-form validity is systematically overestimated. It is argued that present statements of the problem do not lead to a unique solution. The general requirement that an abbreviated test should save time while retaining maximum validity cannot be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
66
0
3

Year Published

1971
1971
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 57 publications
2
66
0
3
Order By: Relevance
“…Several psychometric studies investigated properties of short tests (Burisch, 1997;Gardner et al, 1998;Levy, 1968;Smith, McCarthy, & Anderson, 2000;Stanton et al, 2002) but did not take decision quality into consideration. Research in educational testing and clinical assessment addressed decision quality in the context of classification (e.g., pass-fail decisions, assigning treatments), which is formally similar to cut-score selection (Berk, 1986;Emons et al, 2007;Ercikan & Julian, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several psychometric studies investigated properties of short tests (Burisch, 1997;Gardner et al, 1998;Levy, 1968;Smith, McCarthy, & Anderson, 2000;Stanton et al, 2002) but did not take decision quality into consideration. Research in educational testing and clinical assessment addressed decision quality in the context of classification (e.g., pass-fail decisions, assigning treatments), which is formally similar to cut-score selection (Berk, 1986;Emons et al, 2007;Ercikan & Julian, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Another important issue is the amount of time saved by the use of a short form. Although there is no universally accepted rule for short-form administration time, it has been suggested that an abbreviated scale should reduce testing time by at least 50% (Levy, 1968). As Table 5 indicates, eight of the suggested short forms reduced administration time by more than 50%.…”
Section: Discussionmentioning
confidence: 99%
“…In a cogent review of short form tests Levy (1968) stated that 'the general requirement that an abbreviated test should save time while retaining maximum validity cannot be satisfied in the absence of a statement about the relative utility of 'time saved' and 'validity lost'. In this connection, although we have not abbreviated a test, we may note that while it is difficult to estimate what validity might be lost by using the three-minute reasoning test instead of the AH4, in terms of the amount of time saved the threeminute test is approximately ten times as quick as the AH4 (and, in addition, it is much easier to score).…”
Section: Discussionmentioning
confidence: 99%